BIODIVERSITY OF ENTOMONEMATODES PARASITIZING SOIL PEST WHITE GRUBS (SCARABAEIDAE) OF BUENOS AIRES, ARGENTINA - Camino, Nora B. (2014)
This work was carried out between 2006-2010 in wheat fields of the Pampas, Argentina, in order to examine the species of nematode parasites and pathogens of white grubs, soil major pest. Samples were taken with shovel in randomly selected sites. Nymphs of Diloboderus abderus and Cyclocephalla signaticollis (Scarabaeidae) were collected. Thirteen species of nematodes belonging to 5 families (Mermithidae, Thelastomatidae, Travassosinematidae, Diplogasteridae and Rhabditidae) were identified. The richness of species values were 1 for Cyclocephalla signaticollis and 12 for Diloboderus abderus. The thelastomatids and rhabdítids were the largest group of nematodes, with a total of 3 species each. The thelastomatids were very prevalent with infections exceeding 60%, followed by diplogasterids which reached 36%. The mermithids were less prevalent with values close to 10%. The family Travassosinematidae had the lowest abundance (0.32). Knowledge of nematode community will be a great value to interpret hostparasite relationships and in many cases determine those species best potential bioregulators important agents in agricultural areas of Argentina. This study is the first in the Pampas region of Argentina to provide a list of white worms parasitic nematodes.